Potensi Ekonomi Wilayah Cepat Maju dan Cepat Tumbuh di Provinsi Jawa Barat - Sumiyarti; Dwi Putra Tegar Naufal (UIR Press, 2019)
The potential leading sector of a region is one of the pieces of information needed in regional development planning. The availability of data on the potential of leading regional sectors will make it easier for development planners to develop more targeted development strategies and policies. This study aims to determine and analyze the potential of leading sectors in West Java Province. The areas that are the focus of the study are in areas that are included in the fast-forward and fast-growing region based on the Klassen typology. The Location Quotient (LQ) method will be applied to determine the potential of leading sectors in these regions. This study also uses the shift-share analysis method to determine the factors that drive growth in these areas. This study utilizes secondary data in the form of district and city GRDP values in the province of West Java in the period 2012-2016. Data processing using cluster analysis gives the results that there are five regions that are categorized as fast-growing and fast-growing regions, namely Bogor Regency, Purwakarta Regency, Karawang Regency, Bandung City, and Cimahi City. While processing using the LQ method gives the results that in the five regions there are a number of sectors that are the basis or potential sectors to be developed. Furthermore, from the shift-share analysis, the results show that some leading sectors have a role in supporting regional economic growth through both comparative and competitive advantages owned by these basic sectors. In general, this study concludes that economic growth in fast-growing and fast-growing regions in the province of West Java is supported by the existence of base sectors that have comparative and competitive advantages, most of which are in the industrial and service sectors.